Mutual coordination of behaviors in human–chimpanzee interactions: A case study in a laboratory setting - Akira Takada (Revue de Primatologie)
This study deepens our understanding of sociality established between chimpanzees and humans by analyzing the sequential organization of interactions in a laboratory setting. We conducted an interaction analysis of two short video clips that recorded a physical measurement event at the Great Ape Research Institute (GARI), Tamano, Japan. The results indicated that captive chimpanzees demonstrated how they perceived their situation, or what they would like, using various kinds of body movements and vocal sounds including hand gestures, scratching, whimpers, and screaming. Human trainers also enacted various meanings using body movements and verbal utterances. In particular, they encouraged chimpanzee–human interactions to include turn-taking, a distinctive style of human communication, by introducing various types of adjacency pairs. They also used other types of utterances, such as providing comments to clarify chimpanzee behaviors to smooth the flow of interactions when a chimpanzee was unlikely to provide a clear response. Analyses of the accumulated interactional histories revealed that most captive chimpanzees and humans in GARI appear to have formed mutually coordinated interaction patterns despite the differences in available semiotic resources between the two species. One exception was an infant chimpanzee raised by humans, who had not yet accumulated a sufficient interactional history to form stable interaction patterns with other chimpanzees. This caused serious problems for the infant and other chimpanzees, making it difficult for them to get along. Our results suggest that captive chimpanzees can adapt to live in accordance with the rhythm of humans in an environment largely constructed by humans, and that humans can coordinate their actions in accordance with the rhythm of chimpanzees. These findings are particularly important and suggest that analyses of human–chimpanzee interactions may help inform research about the foundations of societies built by humans, built by chimpanzees, and co-built by humans and chimpanzees.